Effects of the proposed Licensing of Businesses Bill on migrant traders in Soweto - Motsoeneng, Mbali (My University, 2017)
As an economic hub of Africa, South Africa has been experiencing an influx of economic and political migrants leading to the ethnic diversification of its population. This trend has incited a xenophobic atmosphere due to frustrations from locals, and has led to violent attacks towards foreign nationals. In particular, the Somali population has endured a high number of attacks as this group has successfully penetrated the informal business market in the townships of South Africa. Government has responded to these xenophobic attacks by proposing, amongst others, a Licensing of Businesses Bill in 2013. The bill has been criticised by the public as it is considered a hostile policy that aims to enforce regulations that restrict foreign nationals from operating businesses in the informal sector. This political dilemma has also led to questions as to how this policy response may have an effect on social cohesion in unequal societies where violence against Somalis is prevailing. The Klipspruit community was selected as it forms part of the City of Johannesburg that has a significant amount of Somali informal traders. The purpose of the study was to examine the root causes of violence against Somalis and the potential of the governments’ policy response to mitigate this phenomenon. In particular, the study also investigated the effect of the proposed Licensing of Businesses Bill on social cohesion development between Somalis and South Africans in Klipspruit. The qualitative research findings indicate that violence against Somalis was due to the economic situation, lack of regulation, competition and business miscommunication. The responses were generally driven by the perception that the government of South Africa introduced a bill that is fostered by nationalistic interests to the detriment of foreign nationals such as Somalis. It is therefore recommended that the government develops a way to enhance power sharing in decision-making processes, monitoring and correcting inequalities amongst culturally distinct groups, promoting cultural diversity and integration through education and lastly ensuring that the government acts in a constitutional manner.
Research presented for the degree of Master of Management in the field of Public and Development Management to the Faculty of Commerce, Law and Management of the University of Witwatersrand. March 2016
Keywords: Informal sector (Economics)--South Africa; Migrant labor--South Africa--Economic conditions; Immigrants--South Africa--Economic conditions; Xenophobia--South Africa; License agreements--South Africa